Killer Cell Immunoglobulin-Like Receptor Haplotype B Modulates Susceptibility to EBV-Associated Classic Hodgkin Lymphoma - Jiang, Peijia; Nolte, Ilja M.; Hepkema, Bouke G.; Stulp, Marijke; van den Berg, Anke; Diepstra, Arjan (Frontiers in Immunology, 2022)
Tumor cells of classic Hodgkin lymphoma (cHL) are derived from antigen presenting B cells that are infected by Epstein Barr virus (EBV) in ~30% of patients. Polymorphic Killer cell immunoglobulin-like receptors (KIRs) expressed on NK cells interact with human leukocyte antigen (HLA) class I and play a key role in immune surveillance against virally infected cells and tumor cells. We investigated the effect of KIR types on cHL susceptibility overall (n=211) and in EBV-stratified subgroups using the Dutch GoNL cohort as controls (n=498). The KIR haplotype B frequency was significantly different between EBV+ and EBV− cHL patients (62% vs. 77%, p=0.04) and this difference was more pronounced in nodular sclerosis (NS) cHL (49% vs. 79%, p=0.0003). The frequency of KIR haplotype B was significantly lower in EBV+ NS cHL compared to controls (49% vs. 67%, p=0.01). Analyses of known KIR – HLA interaction pairs revealed lower carrier frequencies of KIR2DS2 – HLA-C1 (29% vs. 46%, p=0.03) and KIR2DL2 – HLA-C1 (29% vs. 45%, p=0.04) in EBV+ NS cHL patients compared to controls. KIR haplotype B carriers are less likely to develop EBV+ NS cHL, probably because of a more efficient control over EBV-infected B cells.